Evolving temperature dynamics in Canada: Preliminary evidence based on 60 years of data - Robert A. Amano; Marc-André Gosselin; Julien Mc Donald-Guimond (Bank of Canada, 2021)
Recent discussions on climate change have led to an interest in its potential impact on economic phenomena and public policy. In this paper, we focus on one aspect of the climate change question by documenting the time-series properties of temperatures across Canada. In particular, we examine the evolving dynamics of daily average temperature and diurnal temperature range (the difference between the daily maximum and minimum temperatures at a given location) for select Canadian cities using data from the past 60 years. While rising mean temperature levels in Canada and elsewhere has been well documented, research exploring the other elements of temperature dynamics using modern econometric methods and rich model specifications are sparse. To fill in this gap, we extend the work of Diebold and Rudebusch (2019) and examine the evolution of daily temperature averages, volatility, seasonality and duration. This new evidence provides economists exploring issues related to climate change with a better understanding of the nature of Canadian temperature dynamics and their magnitudes.
Keywords: C22; Q54; 330; Climate change; Econometric and statistical methods